Risk and investment: Evidence from rural Viet Nam - Carol Newman; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper explores the impact of exposure to uninsured risks on the investment decisions of farmers. We distinguish between households' perceived exposure to uninsured risk, measured as past exposure to deviations in average rainfall levels, and the actual realization of shocks. We examine how households cope with the latter in terms of consumption smoothing and the depletion of assets. We also consider the interaction between past weather-risk exposure and the actual realization of weather shocks to ascertain the extent to which the investment strategies of risk-exposed households "pay off" by buffering them in the face of actual shocks. We use panel data on rice farmers in Viet Nam for the 2008-16 period and match this to annual rainfall data. Our results show that households that are exposed to risk invest more in unproductive assets to avoid the downside risk associated with exposure to flooding. This translates into lower income levels. The investment in these assets does not appear to pay off once actual risks are realized.
Keywords: D14; D81; O12; 330; risk; rainfall; weather shocks; investment; risk-coping; Viet Nam